Development of a Pico-Hydro Generating System with SES-BMS for Domestic Use - Azuddin, Muhammad Aiman; Mat Jusoh, Mohammad Azzeim; Che Abdullah, Sukarnur; Mohamed, Zulkifli; Mohd Ramli, Mohd Hanif (International Journal of Integrated Engineering, 2022)
Non-renewable resources have decreased significantly over the past decade, whereas, the current renewable energy system is expensive and more focused on large-scale use. The goal of this project was to design a user-friendly pico-hydro system with a Smart Energy Storage Battery Management System (SES-BMS) to utilize the potential of domestic water flow while saving energy consumption and daily costs. The overall system is a combination of the standard pipeline, a pico-turbine, the SES-BMS and a simple light source. The flow of water is utilized by converting kinetic energy into electrical energy. The design was performed by using the Engineering Design Process (EDP) with coding via Arduino microcontroller. The main outcome of this project was a proof of concept that showed the potential for domestic use of the pico-hydro system combined with the SES-BMS system. Compared to the previous mini-hydro design, the new system showed an increase in performance during the average flow rate in the domestic pipeline, generating an improved value of 68 mW of power during the flow rate of 0.075 x 10-3 m3/s. An optimal charging time of 10 hours is recommended to accommodate the 3.5-hour use of a 12W LED lamp, to maintain the stability and reliability of the system, especially the battery pack.